Implementing PMIPv6 Protocol Based on Extended Service Set for IEEE 802.11 Infrastructure WLAN - Deqing Zhu; Lin Xu; Yi-hua Zhu; Xianzhong Tian (International Journal of Distributed Sensor Networks)
With the popularity of IEEE 802.11 based wireless fidelity (Wi-Fi) portable devices, it becomes increasingly significant to support the mobile users carrying Wi-Fi devices to access the Internet of Things (IoT) so that the communications between the mobile users and the smart objects deployed in the IoT stay uninterrupted when the mobile users are in movement. A scheme using Extended Service Set- (ESS-) based architecture is presented to implement the proxy mobile IPv6 protocol, that is, PMIPv6, for IEEE 802.11 infrastructure Wireless Local Area Networks (WLANs). The key signaling packets together with their time sequences for the mobility management in the proposed scheme are proposed. Moreover, the handoff delay in the proposed scheme is derived, through which the performance of the proposed scheme is analyzed. Numerical analysis indicates that the proposed scheme considerably outperforms the existing scheme that uses the Basic Service Set (BSS) based architecture in terms of handoff delay in the case when the delay between Mobile Access Gateway (MAG) and local mobile anchor (LMA) is relatively large.